Experimental evidence that livestock grazing intensity affects cyclic vole population regulation processes. Issue 1 (8th September 2013) - Villar, Nacho; Cornulier, Thomas; Evans, Darren; Pakeman, Robin; Redpath, Steve; Lambin, Xavier
Abstract: Grazing by domestic ungulates may limit the densities of small herbivorous mammals that act as key prey in ecosystems. Whether this also influences density dependence and the regulation of small herbivore populations, hence their propensity to exhibit multi‐annual population cycles, is unknown. Here, we combine time series analysis with a large‐scale grazing experiment on upland grasslands to examine the effects of livestock grazing intensity on the population dynamics of field voles ( Microtus agrestis ). Using log‐linear modelling of replicated time series under different grazing treatments, we show that increased sheep densities weaken delayed density dependent regulation of vole population growth, hence reducing the cyclicity in vole population dynamics. While population regulation is commonly attributed to both top‐down and bottom up processes, our results suggest that regulation of cyclic vole populations can be disrupted by the influence of another grazer in the same trophic level. These results support the view that ongoing changes in domestic grazing intensity, by affecting small mammal dynamics, can potentially have cascading impacts on higher trophic levels, and strongly influence the dynamics of upland grassland systems.